An evaluation of Internal Communication at a selected University of Technology (UoT) in Gauteng Province - Moimane, Nontobeko Zakhona (Vaal University of Technology, 2024)
This study provides comprehensive insights into internal communication strategies and their evaluation, illuminating the intricacies of employer-employee relationships in the communication context. Recognising internal communication's pivotal role in organisational success, it underscores the necessity of understanding and refining communication strategies. Effective internal communication, marked by enhanced employee competence, favourable attitudes, increased productivity, retention, and satisfaction, underscores the imperative to optimise communication methodologies. The research methodology employed a quantitative approach, leveraging SPSS for data analysis, particularly focusing on descriptive statistics to determine demographic patterns and organisational profiles among respondents. This methodological choice, grounded in objectivity and a positivistic perspective, aimed to ensure precision and reliability in analysing data obtained from a specific University of Technology (UoT) in South Africa. Quantitative research, noted for its breadth, statistical descriptions, and generalisability, facilitated the exploration of relational questions concerning dependent and independent variables within internal communication dynamics. The study highlights the significance of evaluating internal communication strategies to foster stronger communication between management and employees. This recommendation, aligned with understanding employees' perceptions of internal media, emphasises the need for a nuanced approach to message content and delivery formats. It advocates for initiatives such as ensuring email access for all employees, installing electronic billboards for easy access to notices, and implementing intercoms for urgent communications, managed by the institution's Advancement Division. Drawing on communication theories, the study further highlights the purposeful nature of communication and the varying efficacy of different communication strategies in conveying information effectively. While rich communication strategies like face-to-face meetings foster greater satisfaction with job-related information, moderate strategies such as email and internet platforms benefit technologically adept employees.
MM (PRM) (Public Relations Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Employer-employee relationships; Communication; Corporate communication; Internal communication; Organisational culture; Stakeholder engagement; Dissertation, Academic -- South Africa.; Communication.; Communication in personnel management.